2020
DOI: 10.1186/s12889-020-09536-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mass media on comprehensive knowledge of HIV/AIDS and its spatial distribution among reproductive-age women in Ethiopia: a spatial and multilevel analysis

Abstract: Background Globally, HIV/AIDS remains a significant public health issue particularly in Sub-Saharan Africa. Media exposure plays a significant role in raising community knowledge about HIV. Therefore, this study aimed to investigate the effect of media on comprehensive knowledge of HIV and its spatial distribution among reproductive-age women in Ethiopia. Methods A secondary data analysis was done based on the 2016 Ethiopian Demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 28 publications
9
37
1
Order By: Relevance
“…At the contextual level, wealth status (poorest, poorer, middle, Richer, Richest), Region (Western Cape, Eastern Cape, Northern Cape, Free State, KwaZulu-Natal, Northwest, Gauteng, Mpumalanga, Limpopo), type of residence (urban, rural) was considered. These variables were not just considered arbitrarily, but based on previous studies in sub-Saharan Africa [18][19][20] including South Africa [21][22][23].…”
Section: Independent Variablesmentioning
confidence: 99%
“…At the contextual level, wealth status (poorest, poorer, middle, Richer, Richest), Region (Western Cape, Eastern Cape, Northern Cape, Free State, KwaZulu-Natal, Northwest, Gauteng, Mpumalanga, Limpopo), type of residence (urban, rural) was considered. These variables were not just considered arbitrarily, but based on previous studies in sub-Saharan Africa [18][19][20] including South Africa [21][22][23].…”
Section: Independent Variablesmentioning
confidence: 99%
“…For example, educated women might be able to easily comprehend the health education they receive compared to uneducated women (27). Also, previous studies have espoused that higher socio-economic status is associated with easy access to healthcare including health information (26,28-30) Furthermore, women who have attained higher education are more likely to secure jobs with high wages and are able to afford various means to access health information (26) Similar to previous studies, (17,19,27,31), place of residence and regional variations were observed in the knowledge of women on MTCT of HIV and AIDS.…”
Section: Discussionmentioning
confidence: 64%
“…Women in urban areas are more likely to have knowledge compared to those in rural areas. This perhaps is due to the inter-regional and rural-urban differentials in access to education and resources including HIV and AIDS education (17,19,27). Liyeh et al (2020) also noted that women in urban centres there is easy accessibility and availability of nearby health services and greater media exposure compared with rural areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations